Never solve each expression. Solve by assigning values of x and y
Let x = 6, y = 2 Therefore, required x – y = 4
x*y = 6^{2} – 2^{2} = 32
x-y = = 3
x+y = 6 x 2 = 12
= 6 + 2 = 8
a) 32-12 = not equal to 4
b) 8*3 = 8^{2} - 3^{2} = 55 not equal to 4
c) 32 - 8 = = 4
d) 12*3 = 12^{2} - 3^{2} not equal to 4
Answer choice (C).
Correct Answer: (x*y) - ()
All features of the online course, including the classes, discussion board, quizes and more, on a mobile platform.
Download videos onto your mobile so you can learn on the fly, even when the network gets choppy!